A Fibonacci control system with application to hyper-redundant manipulators. Issue 2 (June 2016) - Lai, Anna; Loreti, Paola; Vellucci, Pierluigi
Abstract We study a model for snake-like robots based on the Fibonacci sequence. The present paper includes an investigation of the reachable workspace, a more general analysis of the control system underlying the model, its reachability and local controllability properties. In addition, we establish some fractal properties of the reachable workspace by means the theory of iterated function systems.